A spray-filming, tissue-adhesive, and bioactive polysaccharide self-healing hydrogel for skin regeneration. (May 2022) - Wu, Shuyuan; Zhang, Zhuojun; Xu, Ran; Wei, Shuo; Xiong, Feng; Cui, Wenzhuo; Li, Biyun; Xue, Ye; Xuan, Hongyun; Yuan, Huihua
Graphical abstract: Highlights: Double cross-linked for self-healing polysaccharide hydrogel fabrication. The rapid gelation time make the hydrogel have spray film-forming ability. The hydrogel exhibited a superior adhesion and hemostatic property. The hydrogel also showed antibacterial property and good biocompatibility. CM loaded hydrogel could enhance the biocompatibility and wound repair ability. Abstract: Developing multifunctional self-healing hydrogels as wound dressings, including strong tissue adhesion, spray film-forming ability, and excellent bioactivity, are highly desired for full-thickness skin wound healing applications. In this study, chondroitin sulfate (CSA) was firstly oxidized to aldehyde-based chondroitin sulfate (OHC-CSA), and then dopamine (DA) was grafted onto OHC-CSA to form OHC-CSA-DA. Thereafter, the OHC-CSA-DA and carboxymethyl chitosan (COOH-CS) based hydrogel (CSA-DA-CS) was successfully fabricated through integrating enzymatic crosslinking, Schiff base and hydrogen bonding interactions. The optimum adhesive strength of the hydrogel was obtained by an orthogonal design when the concentrations of polymer, HRP enzyme, and H2 O2 were 30 mg/mL, 0.24 U/mL, and 0.00085%, respectively. This novel hydrogel showed rapid self-healing performance, robust mechanical strength and strong adhesion, spray film-forming ability, hemostatic property, antibacterial property and good biocompatibility, which are beneficial to function as a wound dressing. Besides, the addition of mesenchymal stem cell-conditioned medium (CM) can further improve the biocompatibility and wound repair ability of the hydrogel.Therefore, this novel hydrogel is an outstanding wound dressing candidate for full-thickness wound healing.